CAR-T cell manufacturing: Major process parameters and next-generation strategies - Ayala Ceja, Melanie; Khericha, Mobina; Harris, Caitlin M; Puig-Saus, Cristina; Chen, Yvonne Y (The Journal of experimental medicine, 2024)
Chimeric antigen receptor (CAR)-T cell therapies have demonstrated strong curative potential and become a critical component in the array of B-cell malignancy treatments. Successful deployment of CAR-T cell therapies to treat hematologic and solid cancers, as well as other indications such as autoimmune diseases, is dependent on effective CAR-T cell manufacturing that impacts not only product safety and efficacy but also overall accessibility to patients in need. In this review, we discuss the major process parameters of autologous CAR-T cell manufacturing, as well as regulatory considerations and ongoing developments that will enable the next generation of CAR-T cell therapies.